Key Factors in Interdisciplinary Interactive Exhibition Design: Exhibition Design Processes with Museum Professionals and Interaction Design and Technology Experts - Bodin, Tora; Duvanå, Daniel (My University, 2021)
This paper describes the process of identifying key aspects present in the processes for interactive exhibition design with special regard to the interdisciplinary nature of projects where internal museum professionals and external interaction design and technology experts must collaborate on design aspects. In a case study with one of Sweden’s largest science centers, 13 interviews were conducted with participants involved in exhibition development projects and other members of the science center’s staff. The interviews were thematically analysed to identify interdisciplinary design challenges and key aspects that affected the perceived outcome of an exhibition, and the observations were validated through a questionnaire sent to interviewed participants and staff at other science centers and museums in Sweden. Our results describe three phases in the exhibition design process as especially important: i) understanding of the design space between museum professionals and interaction design and technology experts,(ii) iterative design with museum professionals and interaction design and technology experts and (iii) launch, evaluation and long-term maintenance strategies for exhibitions between museum professionals and interaction design and technology experts. The primary contribution of this work is additional insight into the less often described design processes for exhibition projects with museum professionals and external contractors and collaborators. It serves to provide an overarching understanding of the exhibition design space and its challenges and should be particularly useful to introduce new participants and actors to these complex interdisciplinary collaborations.
Keywords: Interaction design; exhibition design; museum design; co-design; collaboration; design processes; ideation; prototyping; testing